Synthesis and self-cleaning properties of superamphiphobic coatings based on burr-like copolymer particles. (4th March 2022) - Zhao, Xia; Duan, Yanping
ABSTRACT: Superhydrophobic and superoleophobic surfaces are widely used in many fields. Inspired by the structure of water strider legs, we proposed a simple method to construct a superamphiphobic surface based on burr-like KH-PS (copolymer of styrene and γ-Methacryloxypropyl trimethoxy silane) nanoparticles by soap-free emulsion polymerization and hydrolytic condensation reaction. In order to improve the film-forming properties and adhesion between coating and substrate, fluoromonomer-containing polysiloxane acrylate (PA) is designed and synthesized to bond burr-like nanoparticles. Then modify the fluorine-containing material on the surface of the burr-like particles to reduce the surface energy. The contact angles of the coating to water, diiodomethane, hexadecane, soybean oil, and rapeseed oil are 164.2° ± 1.5°, 155.3° ± 1.7°, 148.6° ± 1.9°, 152.7° ± 1.6°, and 153.5° ± 1.7°, respectively. The superamphiphobic coating exhibits excellent thermal stability, chemical stability, and self-cleaning performance. The microscopic roughness of coating constructed by organic polymer particles has broader application prospects on soft substrates such as fabrics.